2019
DOI: 10.1186/s13020-019-0280-7
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing network pharmacology to explore the underlying mechanism of Radix Salviae in diabetic retinopathy

Abstract: Introduction: Radix Salviae (Dan-shen in pinyin), a classic Chinese herb, has been extensively used to treat diabetic retinopathy in clinical practice in China for many years. However, the pharmacological mechanisms of Radix Salviae remain vague. The aim of this study was to decrypt the underlying mechanisms of Radix Salviae in the treatment of diabetic retinopathy using a systems pharmacology approach.Methods: A network pharmacology-based strategy was proposed to elucidate the underlying multi-component, mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…Recently, network pharmacology has been gradually used in the field of Chinese medicine to investigate the pharmacologic mechanisms [31][32][33]. In this study, network pharmacology was applied to analyze the interaction between SCR and PID and the selection of critical targets.…”
Section: Network Constructionmentioning
confidence: 99%
“…Recently, network pharmacology has been gradually used in the field of Chinese medicine to investigate the pharmacologic mechanisms [31][32][33]. In this study, network pharmacology was applied to analyze the interaction between SCR and PID and the selection of critical targets.…”
Section: Network Constructionmentioning
confidence: 99%
“…Utilizing a network pharmacology approach, Piao [17] found that MMP9 and IGF-1 (an IGF family member contained in Radix salviae) may be key therapeutic targets in DR. Consistent with Piao's result, we found that MMP9 was included in both the CXC and HXMMT I-T networks.…”
Section: Discussionmentioning
confidence: 99%
“…Network pharmacology is an emerging discipline that builds and analyzes biological networks based on systems biology to reveal the role of drugs and their mechanisms [13,14]. By constructing a "componenttarget-pathway" research network, we can observe how drugs act on multiple targets at the same time, thereby regulating multiple signal pathways, comprehensively reveal their drug e cacy network, and explain their mechanism of action [15].…”
Section: Introductionmentioning
confidence: 99%